The nutrition effects of sugarcane cropping in a southern Philippine province - Bouis, Howarth E.; Haddad, Lawrence J. (International Food Policy Research Institute, 1994)
This chapter summarizes findings on the nutrition effects of commercialization of agriculture in Bukidnon Province on the southern island of Mindanao in the Philippines. This region was engaged primarily in semisubsistence corn production until the establishment of a sugar mill led to a rapid expansion of sugarcane production in the area. The Bukidnon Sugar Company (BUSCO), which began operations in 1977, was established in response to high world sugar prices. Cane production was sufficiently profitable to generate a high demand for contracts by nearby farmers, so the mill's capacity was expanded in 1981.